The Threat Of Tax Evasion Practices In the Coal Mining Sector In Indonesia On Economic Security - Irmayanti, Dian Putri; Yulivan, Ivan; Widyarsih, AV. Rahajeng (Educoretax, 2024)
This research examines tax evasion practices in Indonesia’s coal mining sector, with a focus on identifying methods used and the role of state intelligence in addressing them. Using a qualitative approach, the study collected data through in-depth interviews with government officials, academics, and industry practitioners. The findings reveal six primary tax evasion practices: illegal mining, income and expense manipulation, document bribery, transaction manipulation, and document falsification. These practices significantly reduce state revenue and undermine the integrity of the coal mining sector. Additionally, the analysis emphasizes the importance of early detection and warning efforts by intelligence agencies to combat tax evasion. The study also underscores the need for improved collaboration among government entities and the utilization of information technology to integrate data and strengthen law enforcement.